Molecular epidemiology of blastocystosis in Malaysia: Does seasonal variation play an important role in determining the distribution and risk factors of Blastocystis subtype infections in the Aboriginal community? - Noradilah Samseh Abdullah; Moktar N.; Anuar T.S.; Lee I.L.; Salleh F.M.; Manap S.N.A.A.; Mohtar N.S.H.M.; Azrul S.M.; Abdullah W.O.; Nordin A.; Abdullah S.R. (BioMed Central Ltd., 2024)
Indexed by WOS/Scopus/ERA